A molecular switch in immunodominant HIV-1-specific CD8 T-cell epitopes shapes differential HLA-restricted escape - Kløverpris, Henrik N; Cole, David K; Fuller, Anna; Carlson, Jonathan M.; Beck, Konrad; Schauenburg, Andrea J; Rizkallah, Pierre J; Buus, Søren; Sewel, Andrew K; Goulder, Philip (Retrovirology, 2015)
Presentation of identical HIV-1 peptides by closely related Human Leukocyte Antigen class I (HLAI) molecules can select distinct patterns of escape mutation that have a significant impact on viral fitness and disease progression. The molecular mechanisms by which HLAI micropolymorphisms can induce differential HIV-1 escape patterns within identical peptide epitopes remain unknown.